The Effect of Husbands' Social Support and Hardiness on Work-Family Balance in Women Entrepreneurs - Dias Adelisyah; Ismarli Muis; Hilwa Anwar (Greenation Publisher & Yayasan Global Research National, 2026)
Women entrepreneurs who are married and have children face dual responsibilities in managing business activities and family life, requiring adequate resources to achieve work-family balance. This study aimed to examine the effect of husbands' social support and hardiness on work-family balance among women entrepreneurs. The study used a quantitative approach with multiple regression analysis. The participants were 309 women entrepreneurs from several regions in Indonesia who were married, had children, and had established, owned, and managed their businesses for at least one year. Data were collected using the Work-family balance Scale, Spousal Support Scale, and Occupational Hardiness Questionnaire. The results showed that husbands’ social support had a positive and significant effect on work-family balance, hardiness had a positive and significant effect on work-family balance, and both variables simultaneously influenced work-family balance. The R square value of 0.628 indicated that the husbands’ social support and hardiness explained 62.8 percent of the variance in work-family balance. These findings emphasize the importance of partner support and resilient personal characteristics in helping women entrepreneurs balance business and family roles.